1988
DOI: 10.1071/bi9880403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C Administration on Serum and Egg-yolk Cholesterol Level of the Chicken

Abstract: Ascorbic acid (vitamin C) was given to 144-days-old layer chickens mixed with their ration at three concentrations: 30, 60 and 90 p.p.m. for 6 months. Cholesterol levels in blood serum (CS) and egg yolk (CE) were measured every 6 weeks (four periods); there was a marked decrease in CS in most treated birds, especially those receiving the highest concentration of vitamin C. There was also a slight decrease in CE in most treated birds. Thyroidal weight showed a significant increase in most treated groups, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Supplementing the vitamin C in poultry diet may have a beneficial effect on performance in such an environment (Combs, 1992;Pardue and Thaxton, 1986;Tillman, 1993). It is also reported that blood and yolk cholesterol were significantly decreased by the addition of vitamin C to the rations (Al-Janabi et al, 1998;El-Gendi et al, 1999). It has been reported that plasma antioxidant vitamins such as vitamin C declined in concentration and oxidative damage increased in stressed poultry (Feenster 1985;Sahin et al, 2002).…”
Section: Introductionmentioning
confidence: 90%
“…Supplementing the vitamin C in poultry diet may have a beneficial effect on performance in such an environment (Combs, 1992;Pardue and Thaxton, 1986;Tillman, 1993). It is also reported that blood and yolk cholesterol were significantly decreased by the addition of vitamin C to the rations (Al-Janabi et al, 1998;El-Gendi et al, 1999). It has been reported that plasma antioxidant vitamins such as vitamin C declined in concentration and oxidative damage increased in stressed poultry (Feenster 1985;Sahin et al, 2002).…”
Section: Introductionmentioning
confidence: 90%
“…Interestingly, PCB administration lowered tissue ascorbic acid and markedly increased urinary excretion of the vitamin. Also of interest is the work of alJanabi et al , 73 who fed high levels of ascorbic acid to laying hens for six months and found marked decreases in serum cholesterol and slight decreases in egg-yolk cholesterol.…”
Section: Vitamin C and Cholesterolmentioning
confidence: 99%